Reciprocal Associations between Depressive Symptoms and Mastery among Older Adults; Black-White Differences - Assari, Shervin; Lankarani, Maryam M. (Frontiers in Aging Neuroscience, 2017)
Purpose: Although higher levels of depressive symptoms and lower levels of sense of mastery tend to be comorbid, limited information exists on racial differences in the longitudinal associations between the two over time. The current study compared Black and White American older adults for the longitudinal links between depressive symptoms and mastery in the United States. Methods: Using data from the Religion, Aging, and Health Survey, 2001-2004, this longitudinal cohort study followed 1,493 Black (n=734) and White (n=759) elderly individuals (age 66 or more) for three years. Depressive symptoms [Center for Epidemiological Studies-Depression scale (CES-D), 8 items] and mastery (Pearlin Mastery Scale, 7 items) were measured in 2001 and 2004. Demographics, socio-economics, and physical health were covariates and race was the focal moderator. Multi-group structural equation modeling was used for data analysis, where groups were defined based on race. Results: Among White but not Black older adults, higher levels of depressive symptoms at baseline predicted a greater decline in sense of mastery over 3 years of follow-up. Similarly among Whites but not Blacks, individuals with lower mastery at baseline developed more depressive symptoms over time. Conclusion: Findings are indicative of Black-White differences in reciprocal associations between depressive symptoms and mastery over time. Race alters how depression is linked to changes in evaluation of self (e.g. mastery) over time.